PERBANDINGAN ASAS-ASAS PERJANJIAN DALAM AKAD JUAL BELI MENURUT HUKUM PERDATA DAN HUKUM ISLAM - Abd. Rahman Shaleh; Imam Fawaid (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2025)
This study aims to analyze and compare the principles of agreements in sales and purchase agreements according to Civil Law and Islamic Law. In practice, sales and purchase agreements are the most common form of agreements carried out in everyday life, both in the national legal system and in the perspective of Islamic law. This study uses a normative legal method with a statutory and conceptual approach, through a literature study of primary and secondary legal sources. The results of the study show that although both legal systems have similarities in emphasizing the importance of agreement (consensualism) and honesty (good faith), there are fundamental differences in the principles of freedom of contract and the prohibition of detrimental elements. Civil Law provides freedom of contract as long as it does not conflict with the law, while Islamic Law limits this freedom by prohibiting the elements of usury, gharar, and maysir. Thus, understanding the comparison of these principles is important to create transactions that are fair, legitimate, and in accordance with applicable legal values.